2017
DOI: 10.1111/hepr.12866
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate transaminase–platelet ratio and Fibrosis‐4 indices as effective markers for monitoring esophageal varices in HIV/hepatitis C virus co‐infected patients due to contaminated blood products for hemophilia

Abstract: In patients co-infected with HIV/HCV due to contaminated blood products for hemophilia, APRI and FIB4 are effective for monitoring esophageal varices, even among patients who are apparently doing well with good liver function as Child-Pugh grade A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Acoustic radiation force impulse is a reliable and reproducible assessment method with favorable intra‐ and interobserver levels of agreement, although there are some limitations . The Fibrosis‐4 (Fib‐4) index and aspartate aminotransferase to platelet ratio index (APRI), which are non‐invasive and accessible serum LF markers, were originally proposed for assessing the severity of LF in CHC patients . Their usefulness in both CHB and CHC patients has been confirmed …”
Section: Introductionmentioning
confidence: 99%
“…Acoustic radiation force impulse is a reliable and reproducible assessment method with favorable intra‐ and interobserver levels of agreement, although there are some limitations . The Fibrosis‐4 (Fib‐4) index and aspartate aminotransferase to platelet ratio index (APRI), which are non‐invasive and accessible serum LF markers, were originally proposed for assessing the severity of LF in CHC patients . Their usefulness in both CHB and CHC patients has been confirmed …”
Section: Introductionmentioning
confidence: 99%
“…reported that the APRI and FIB‐4 score are effective to detect esophageal varices in HIV/HCV coinfection . They concluded that even though a patient is apparently doing well with good liver function as Child–Pugh grade A, their physician should consider consulting a hepatologist to rule out esophageal varices when the patient shows high APRI/FIB‐4 values . Furthermore, Yoshimoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is known that compensated cirrhosis in co‐infected patients may progress rapidly to decompensated liver cirrhosis (liver failure) by an episode of liver encephalopathy, 7 and difficulties when LT is considered involve judgment of the timing of surgery as well as perioperative management 8 . In view of the current situation as mentioned above, our research group has examined the liver function of the co‐infected patients from various viewpoints and suggested inclusion criteria for DDLT 9,10 …”
Section: Introductionmentioning
confidence: 99%